Technical efficiency and total factor productivity changes in European dairy farm sectors - Fabio A. Madau; Roberto Furesi; Pietro Pulina (Agricultural and Food Economics, 2017)
Abstract This paper aims to evaluate the technical efficiency and the total factor productivity change of dairy farms in EU countries. Analyses were carried out in order to determine which countries showed the best performance adaptations when the quota regime was relaxed and to evaluate the technical conditions of European farmers at the starting point of the new regime (milk quota abolition). A data envelopment analysis (DEA) was applied on aggregate data related to 22 European countries for the period from 2004 to 2012. The findings suggest that milk farms show small scope for improving efficiency using their own technical input. The estimation of total factor productivity and its components suggest that the European milk sector has suffered a decline in productivity. This means that external factors, independent of the farmers’ capacity to use technical inputs, can play a greater role than efficiency in conditioning productivity and profitability in the near future.